A Randomized Controlled Trial Comparing Two Multimodal Analgesic Techniques in Patients Predicted to Have Severe Pain After Cesarean Delivery. Issue 6 (December 2016) - Booth, Jessica L.; Harris, Lynnette C.; Eisenach, James C.; Pan, Peter H.
Abstract : (Abstracted from Anesth Analg, 122:1114–1119, 2016) Postoperative pain after cesarean delivery that is inadequately treated is a notable source of patient morbidity. It also may increase the risks of postpartum chronic pain and depression.